SARCOPENIA – CURRENT KNOWLEDGE AND CLINICAL CHALLENGES - Mateusz Kacalak; Zofia Nowakowska; Julia Szklarska-Komenda; Maciej Komenda; Wiktoria Dybizbańska; Aleksandra Marek; Agnieszka Burzej; Krzysztof Jamroch; Karolina Dziki; Katarzyna Garncarz (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Sarcopenia, defined as the progressive loss of muscle mass and strength, is one of the primary threats to the functional independence of older adults. With global population aging and an increasing burden of chronic diseases, the clinical relevance of this condition continues to grow. Despite rising awareness, sarcopenia remains underdiagnosed and undertreated, leading to a decline in quality of life, a higher risk of falls, hospitalizations, complications, and increased mortality. Aim of the Study: The aim of this study is to provide a comprehensive review of current knowledge on sarcopenia, including its definition, pathophysiology, epidemiology, risk factors, diagnostic criteria, and therapeutic and preventive strategies. Methodology: A literature search was conducted using PubMed, Google Scholar, and ScienceDirect for publications from 2005 to 2025. The review included peer-reviewed studies, clinical trials, systematic reviews, and international guidelines (EWGSOP2, ICFSR, GLIS) related to the definition, diagnosis, and management of sarcopenia. Only peer-reviewed articles published in English were included, while non-peer-reviewed materials, conference abstracts, and case reports without broader applicability were excluded. Conclusions: Sarcopenia is a complex and increasingly prevalent condition that requires early diagnosis and a comprehensive, multidisciplinary approach. Effective management relies primarily on resistance training, adequate protein intake, and correction of nutritional deficiencies, while pharmacological options remain limited. Particular attention should be directed to secondary sarcopenia, and routine screening in at-risk populations is essential to reduce functional decline and adverse health outcomes.